Análisis de las operaciones crediticias en la "Fundación ESPOIR" y su incidencia en l desarrollo empresarial de microempresarios de Quevedo durante el año 2009. - Peña Haro, Fabián Leonardo (2010)
The expansion of the microenterprise sector responds, first to the cyclical unemployment that defines it as a necessity: to create the job itself, and secondly, new organizational trends of companies, as a result of crisis are reducing their size and tend to outsource work in small businesses. Goods and services they produce are for the market and act in almost all sectors of activity. According to these sources and their degree of evolution can be classified in subsistence activities where mainly primary micro entrepreneurs not given the phenomenon of capital accumulation. With multiple sources of income, the employer uses the net income for consumption without further reinvestment. They operate from the logic of individual or family reproduction. Activities from very poor, unstable and marginal linkages with the market and little chance to generate some kind of surplus. They use small loans, short term and for working capital, and have the capacity and willingness to pay high interest rates if the loan is accessible and appropriate them. Business expansion that essentially are limited to guarantee the reproduction and stay in the market in conditions of instability, over-relying on individual effort, and producing a low replacement and remuneration of productive factors, allowing to start a process capital accumulation, primarily by working capital growth of micro and possibly in fixed assets by the gradual incorporation of machines and tools. This is basically family labor and usually the company is in an informal situation, is the main source of income for the family and the benefits are partly reinvested. Demand more flexible financial products.